... og du finder noget nyt : Samling Block. (Kopenhagen : Statens Museum for Kunst, 1992)
Duchamp, Marcel ; Cage, John ; Beuys, Joseph ; Hamilton, Richard ; Broodthaers, Marcel ; Brecht, George ; Filliou, Robert ; Williams, Emmett ; Rot, Dieter ; Kopcke, Arthur ; Unsworth, Ken ; Paik, Nam June ; Vostell, Wolf ; Kabakov, Ilya ; Richter, Gerhard ; Knowles, Alison ; Vautier, Ben ; etc.
Samling / Sammlung / Collection Block, Statens Museum for Kunst, Kopenhagen, 1992
boek